(untitled) (Bangladesh Journal of Medical Science, 2018)
Aims and objectives: to see the efficacy of ultrasonography in the management of amoebic liver abscess. We assessed whether patient required surgery or can be managed with drainage procedure on ultrasonography basis. Materials and Methods: This is a prospective study done from July 2014 to May 2015, in a medical college in remote area. A total of 88 patients diagnosed with liver abscess were included in the study for ultrasound-guided percutaneous aspiration or pigtail drainage management. All patients had been treated with antibiotics or antimicrobials for at least 2 weeks if treated conservatively and were still being continued for another 6 weeks. Results: A total of 88 patients with liver abscess were successfully treated, consisting 79 males and 9 female. The age ranged from 18 to 82 years with a mean of 43.6 years. A total number of 76 (86.36%) cases undergone percutaneous catheter drainage and 12 (13.6%) underwent needle aspiration. A total of 73 (82.95%) patients had single large abscess, while 8 (9%) had two and 7 (7.9%) had multiple abscesses. The abscesses were commonly located on the right lobe of liver. The Pigtail catheters of sizes 10 F to 18 F was introduced either directly under the guidance of the guide wire with safety precautions. The volume of pus aspirated averaged from 70 - 1200 ml, while the period of catheter drainage ranged from 7 to 24 days with the follow up on ultrasonography. Conclusion: This study shows a success rate of ultrasonography almost 98 % by avoiding unnecessary surgical intervention. It was confirmed that needle aspiration in small abscesses and catheter drainage in large abscesses offers the safest and best modality. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.258-262